2021
DOI: 10.1037/rmh0000179
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between access to mental health counseling and interest in rural telehealth.

Abstract: Telehealth has been proposed as a strategy to reduce disparities in access to mental health counseling in rural areas. The objective of this study was to compare interest in telehealth between rural and urban communities and to identify the factors that impact interest in using telehealth services. A sample of 2,010 respondents completed a cross-sectional survey addressing issues of access to mental counseling and interest in telehealth in both rural and urban areas. Survey data were collected in October-Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…These findings are consistent with the prior literature on mHealth for rural populations. For example, a recent study of the association between access to mental health counseling and interest in rural telehealth found that although rural residents have less access to mental health counseling and the internet than urban residents, rural residents have more interest in telehealth [ 48 ]. Additionally, the less access participants had to mental health counseling, the greater their interest in telehealth [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the prior literature on mHealth for rural populations. For example, a recent study of the association between access to mental health counseling and interest in rural telehealth found that although rural residents have less access to mental health counseling and the internet than urban residents, rural residents have more interest in telehealth [ 48 ]. Additionally, the less access participants had to mental health counseling, the greater their interest in telehealth [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Telehealth has seen increased usage through expanded healthcare industry adoption and the recent pressures from the pandemic. One study found an increased interest in telehealth when access to physical services were limited, and this was particularly common in rural areas (Weinzimmer et al, 2021). Rural clinical staff members were able to define telehealth services and uses but expressed concerns for its ability to maintain and use as well as the cost and privacy (McClellan et al, 2020).…”
Section: Telehealthmentioning
confidence: 99%
“…Despite ongoing efforts to address mental health disparities throughout the USA, nearly 135 million Americans continue to reside in mental health shortage areas, with a majority living in rural locations. 1,2 Among the numerous barriers to rural care, distance to services is a primary contributor; patients living further away from healthcare centers have poorer health outcomes. 3 As high-speed internet became more readily available, cheaper, and stable in non-urban locations, telehealth, or the integration of technology with healthcare services (e.g., video, telephone, email), became a frequently suggested method of reaching those who have historically gone without care.…”
Section: Introductionmentioning
confidence: 99%